2008
DOI: 10.1186/1471-2164-9-71
|View full text |Cite
|
Sign up to set email alerts
|

Activation of counter-regulatory mechanisms in a rat renal acute rejection model

Abstract: Background: Microarray analysis provides a powerful approach to identify gene expression alterations following transplantation. In patients the heterogeneity of graft specimens, comorbidity, co-medications and the challenges in sample collection and preparation complicate conclusions regarding the underlying mechanisms of graft injury, rejection and immune regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
3
18
0
2
Order By: Relevance
“…Second, we found that IFϩi was associated with upregulation of immune/ inflammatory pathways linked with acute cellular rejection. [17][18][19][20][21][22][23] The results lend credence to the view that early surveillance histology with or without targeted molecular analysis provides important prognostic information. 10,24 They also suggest that analysis of intragraft innate and adaptive immune pathways during early posttransplantation years 25 may provide the basis for interventions to subvert chronic deterioration in a subset of recipients with clinical expectations of excellent long-term outcome.…”
supporting
confidence: 54%
“…Second, we found that IFϩi was associated with upregulation of immune/ inflammatory pathways linked with acute cellular rejection. [17][18][19][20][21][22][23] The results lend credence to the view that early surveillance histology with or without targeted molecular analysis provides important prognostic information. 10,24 They also suggest that analysis of intragraft innate and adaptive immune pathways during early posttransplantation years 25 may provide the basis for interventions to subvert chronic deterioration in a subset of recipients with clinical expectations of excellent long-term outcome.…”
supporting
confidence: 54%
“…The observance of high MMP-7 expression in the kidney at the time of AR has also been previously reported in chronic kidney rejection, 27 human kidney aging, 28 and a rat renal AR model. 29 MMP-7 is a collagenase-related connective-tissue-degrading metalloproteinase and plays a role in the breakdown of extracellular matrix in normal physiologic processes, tissue remodeling during injury, 30 and neutrophil influx to sites of injury. 31 SERPRING1 regulates leukocyte trafficking and complement (inactivating C1r, C1s, MASP2, and C3b proteases), 32 which is also locally regulated in the kidney during ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the graft leukocyte pattern revealed massive upregulation of nearly all genes of pro-and antiinflammatory cell types analyzed on aTX postoperative day 4 ( (17,18,28,29). Upregulation of these genes (exception: neutrophil granulocytes: CD66, 3.1 6 0.3, P , 0.05) was not detected on aTX postoperative day 1 (meaning that significant graft infiltration had not yet started at that time).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%